طريقة مقترحة لإيجاد الحل الأساسي المقبول (الممكن) لمشكلة النقل - البدري فاتن فاروق; صالح سرمد علوان (Journal of Economics and Administrative Sciences, 2007)
The evaluation process of transportation problem required finding basic feasible solution (bfs). Represent the base of decision making process. To purpose start anther batter solution to able from decisions taking process, consider the decision making process, find (bfs) represent the standard form in linear programming (LP). Most important stage of update (bsf) stages that achieved minimum cost (the optimal solution). the goal of paper to improving & evaluation (bfs) by new procedure (proposed method) comparison with Vogel method.